ANALISIS WACANA SARA MILLS DALAM FILM ANIMASI â€œPEMIMPIN PEREMPUANâ€ KARYA CISFORM UIN SUKA - Meirianti, Mike; choiriyati, Sri; Amirullah, Muhammad ilyas (INTERCODE, 2024)
Film is an effective medium for providing entertainment and information to the public. as in the animated film "Female Leader" by cisform UIN SUKA which succeeded in coloring the Indonesian animated film with different content, not just entertainment but knowledge information with Islamic nuances. In the animated film "Female Leader" tells the pros and cons of choosing a woman as the head of Risma at the Ar-Rahman Mosque, so that in this story a conflict emerges and the resolution is that in fact women are also allowed to be leaders.With Sara Mills' discourse analysis based on her analytical framework. This film depicts the role of men as subjects (tellers) and women as objects (who are told). Where men do not prioritize women's positions, but female actors are the main roles discussed. In this film the author also analyzes that there is a big ideology in the making of this film, namely to change the paradigm, that women can also be leaders with good leadership capacity, and the position of women is not just a complement in a group but as the main figure (chairman) in a group. group. Keywords: Film, Women's Leadership, Discourse Analysis, Ideology